Megapolis as a symbiosis of socio-economic ecosystems: The role of collaboration - Tatyana Olegovna Tolstykh; Leyla Ayvarovna Gamidullaeva; Nadezhda Shmeleva; Sergey Gromov; Alexander Ermolenko (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
In recent years, smart and ecological urbanism and transformations into the new models of city making have become a global mainstream. These are models of the smart city, the eco-city, and the eco-megacity. The article proposes a conceptual approach to the formation of the eco-megacity as a qualitatively new phenomenon in the post-industrial economy. The prerequisites for the transformation of a megapolis into an eco-megacity have been analyzed. The key characteristics of the new phenomenon have been revealed. The role of collaboration as the main factor in increasing the efficiency of interaction processes between ecosystem actors and between ecosystems themselves has been presented. The relationship of the formed ecosystem approaches and the groups of actors during implementation of an institutional project in the megapolis have been determined. It allows for the transformation of a megapolis into an eco-megacity. The ant colony optimization algorithm for studying the symbiosis of socio-economic ecosystems in the megapolis has been proposed. The authors have attempted to contribute to the development of theoretical and methodological aspects of the emerging eco-megacity concept as a new phenomenon of the modern economy.
Keywords: 650; ant algorithm; collaboration process; eco-megacity; ecosystem approach; institutional approach; megapolis transformation; symbiosis